2023
DOI: 10.3390/app13074377
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Alterations in Patients with Mucous Membrane Pemphigoid and Pemphigus Vulgaris: A Systematic Review

Abstract: The human oral cavity comprises an extensive range of microorganisms, viruses, bacteria, fungi, archaea, and protozoa, each having a particular role and interacting with each other and with the host in sickness or health. Changes in the microbiome composition can be crucial in balancing health and disease, locally and systemically. Various microbial species in commensal relationships form the oral microbiota, and when this commensalism undergoes variations the immune system can be pushed towards the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…In a recent pilot study, it was observed that in subjects with pemphigus and BP, there is an imbalance in the oral microbiota, characterized by a reduction in Bacteroidetes and an increase in the phylum Firmicutes and the genus Staphylococcus [ 30 ]. Based on this evidence are new and promising therapeutic approaches, such as probiotics or prebiotics, especially in the adjuvant and prolonged treatment of MMP [ 31 ]. To rebalance the oral microbiota, oral probiotics could be important adjuvant factors to first-line therapies in the long-term management of MMP patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent pilot study, it was observed that in subjects with pemphigus and BP, there is an imbalance in the oral microbiota, characterized by a reduction in Bacteroidetes and an increase in the phylum Firmicutes and the genus Staphylococcus [ 30 ]. Based on this evidence are new and promising therapeutic approaches, such as probiotics or prebiotics, especially in the adjuvant and prolonged treatment of MMP [ 31 ]. To rebalance the oral microbiota, oral probiotics could be important adjuvant factors to first-line therapies in the long-term management of MMP patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 It is well established that intestinal bacteria and their metabolites exert an active role in modulating adaptive immune responses 8,9 ; alterations of the gut microbiota (GM) composition and function have been shown to influence systemic inflammation in several autoimmune diseases, including psoriasis, atopic dermatitis, vitiligo and PV. 10 There is evidence that alterations of the GM influence pemphigus pathology: in one study, enriched Flavonifractor spp. were shown to correlate positively with serum levels of interleukin (IL) IL-17A and IL-21; in the same study, serum levels of IL-17A correlated negatively with both Lachnospiracea_incertae_sedis and Coprococcus genera.…”
Section: Introductionmentioning
confidence: 99%